Inflation Targeting in Dollarized Economies - Leiderman, Leonardo (IMF Working Papers; Working Paper ;, 2006)
The shift to inflation targeting has contributed to the relatively low inflation observed in some emerging market economies although, as noted by many economists, the preconditions required for a successful implementation were not in place. The existence of managed exchange rate regimes, a narrow base of domestic nominal financial assets, the lack of market instruments to hedge exchange rate risks, together with fear of floating and dollarization, have been stressed as factors that might weaken the efficacy of monetary policy. By examining various aspects of monetary transmission and policy formulation in two highly dollarized economies (Peru and Bolivia) vis-a-vis two economies with low levels of dollarization (Chile and Colombia), we found that, while dollarization imposes differences in both the transmission capacity of monetary policy and its impact on real and financial sectors, it does not preclude the use of inflation targeting as a policy regime.